2009
DOI: 10.1111/j.1582-4934.2008.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic transforming capacity of IgG purified from plasma of type 1 diabetic patients

Abstract: We previously demonstrated that plasma of type 1 diabetic patients contains antibodies complexed irreversibly with Grp94 that also display proteolytic activity. In this work, we wanted to test whether antibodies obtained from diabetic plasma may convey an inflammatory risk on vascular cells. To this aim, IgG were purified on the Protein-G column from individual plasma of eight type 1 diabetic patients, and then tested on HUVECs to measure effects on cell growth and morphologic changes at different incubation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…In this work we wanted to address the unsolved question concerning the nature and structure of Grp94-IgG complexes that circulate in plasma of T1 diabetic subjects with still uncertain pathogenetic significance. Previous observations suggested that these complexes could be immune in nature, based on the finding that anti-Grp94 Abs were present in diabetic plasma in response to extracellular exposure of Grp94 [ 8 ]. However, the discovery that Grp94 was able to form rapidly stable complexes also with nonimmune IgG in vitro [ 9 ] raised the possibility that the mechanism leading to the formation of Grp94-IgG complexes in vivo could also exclude an antigenic recognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we wanted to address the unsolved question concerning the nature and structure of Grp94-IgG complexes that circulate in plasma of T1 diabetic subjects with still uncertain pathogenetic significance. Previous observations suggested that these complexes could be immune in nature, based on the finding that anti-Grp94 Abs were present in diabetic plasma in response to extracellular exposure of Grp94 [ 8 ]. However, the discovery that Grp94 was able to form rapidly stable complexes also with nonimmune IgG in vitro [ 9 ] raised the possibility that the mechanism leading to the formation of Grp94-IgG complexes in vivo could also exclude an antigenic recognition.…”
Section: Discussionmentioning
confidence: 99%
“…This was also supported by the finding that anti-Grp94 antibodies are present in diabetic plasma in response to the immune stimulation driven by extracellular Grp94 [ 2 ]. Other observations indicated that Grp94-IgG complexes in diabetic plasma can induce an intense activation of inflammatory cell signaling pathways with angiogenic-like transformation of vascular cells [ 8 ]. This has led to the proposal that Grp94-IgG complexes might be a marker of increased risk of vascular complications in T1 diabetes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility that Grp94 can bind to IgG in a manner different from that predicted from its chaperoning function has been raised in a previous work in which complexes have been observed to form between Grp94 and human non-immune IgG in vitro [25]. Such complexes in addition turned out to be functionally similar to those identified in the plasma of diabetic subjects in whom they drive a high risk of vascular damage [21], [24].…”
Section: Discussionmentioning
confidence: 99%
“…In ex vivo experiments on plasma of type 1 diabetic subjects we observed that Grp94, besides being present at a higher-than-normal concentration [23], circulated only linked to plasma proteins, mostly IgG, forming complexes of various masses prevalently immune in nature [21], [24]. We further demonstrated that Grp94 could also bind to IgG irrespective of their immune nature, forming non-immune complexes (NICs) in which binding occurs at sites other than the antigen-binding site [25].…”
Section: Introductionmentioning
confidence: 91%
“…Previous works had stably demonstrated that when liberated in the extracellular milieu - as it also occurs in autoimmune diseases [27, 31] - Grp94 is never detected as a single protein, but is always found linked in big, stable complexes with IgG [26, 28]. To explore the possibility that Grp94-IgG complexes could also circulate in cancer patients, we first tested any single plasma sample with anti-Grp94 Abs in Western blotting (WB) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%